Equilibrium in International Trade: A Diagrammatic Analysis - Baldwin, Robert E. (Quarterly Journal of Economics, 1948)
I. The problem, 748. — II. One country acts as a monopolist and sets a price which the other accepts, 749. — III. The same, continued, 752. — IV. One country acts as a discriminating monopolist, making an all-or-none offer which the other accepts, 756. — V. The case of pure competition, 759. — VI. Comparison of the three cases, 761.